Efficiency of Attraction to Administrative Responsibility for Providing Financial Support to Terrorism - Yunusov, Viktor V. (Sibirskoe ûridičeskoe obozrenie (Online), 2017)
The effectiveness of bringing to administrative responsibility for providing financial support to legal entities in the Russian Federation is discussed. The analysis of Russian financial monitoring's (Rusfinmonitoring) work on bringing legal entities to administrative responsibility for providing financial support to terrorism is conducted.